PRESENÇA DE CÉLULAS CD57+, CD163+ E DNA PAPILOMAVÍRUS HUMANO NA CAVIDADE ORAL DE PACIENTES COM LEUCOPLASIA E CARCINOMA EPIDERMOIDE ORAL - Jennifer Naed Martins de Freitas (2023)
Oropharyngeal cancer has increased among young people and adults in recent years and has as one of the main causes the human papillomavirus (HPV) infection, which is considered a sexually transmitted infection (STI). Leukoplakia is the most common potentially neoplastic lesion in the oral cavity, with a high risk for developing oral squamous cell cancer. The lesions in the oral cavity have risk factors in common, and there is the possibility that human papillomavirus (HPV) infection may favor malignant transformation in different leukoplastic lesions, thus progressing to oral squamous cell carcinoma (OSCC). The immune system is responsible for eliminating HPV in most infections, however the persistence of the virus is a predisposing factor for malignant transformation of infected cells. NK cells are responsible for eliminating virus-infected cells and tumor cells. Macrophages can be activated by the classical route, where they are called M1 and destroy microorganisms, triggering inflammation, or by the alternative route, being called M2 or tumor-associated macrophages (TAM). The present work aimed to correlate the expression of CD57 (Natural Killer - NK cells) and CD163 (M2 macrophages) to the detection of HPV DNA in patients with leukoplakia and CEO. The participants were selected in the period from 2018 to 2020 in the Clinics of the School of Dentistry of UFMS and the Center for Dental Specialties of the Municipal Health Secretariat of Campo Grande - MS. CEP/UFMS 2.621.049. For HPV detection by Nested PCR, exfoliated cells obtained from the surface of the lesions were collected and after this collection, patients underwent surgical procedures for biopsy of the lesions, used for histopathology and immunohistochemistry. The frequency of HPV DNA detection among the research participants was 27.78% (10/36). Lesions were classified as Epithelium Without Dysplasia (n=6), Discrete Epithelial Dysplasia (n=7), Moderate Epithelial Dysplasia (n=9) and CEO (n=17). In specimens histologically classified as CEO, the expression of CD163 (M2 macrophages) was higher (4456.32 cels/mm3), whereas the expression of CD57 (NK cells) was lower (2741.05 cels/mm3). There was no relationship between positivity for HPV DNA and the expression of CD163 and CD57 (p>0.05). There was no relationship between HPV DNA positivity and histopathological findings. High expression of CD163 and lower expression of CD57 in tissues with CEO represents a worse prognosis considering the pro-tumor activity of M2 macrophages and lower amount of NK cells that could eliminate tumor cells containing tumor progression. Keywords: Oral Cavity, Epithelial Dysplasia, Immunohistochemistry.